A new control chart based on the loess smooth applied to information system quality performance. (1st January 2012) - Tao, Zhi; Liu, Fengkun; Shen, Fanglin; Suh, Michael; Booth, David
Sometimes to measure the performance of an information system, unusually long response times of database operation need to be identified. Compared with Lloyd's (1995) statistical process control chart, we propose an outlier resistant robust locally weighted scatterplot smooth (loess) based control chart that identifies effectively all the out of control points of operation in Lloyd's (1995) data. Our findings provide guidance to management in information system quality control and more generally to all control chart users in cases where outliers occur in the charted data.